Kegiatan Supervisi Kepala Sekolah dengan Teknik Group Discussions Secara Daring untuk Meningkatkan Kemampuan Guru dalam Menyusun Soal Tes Hasil Belajar Di SDN Pesantren Kabupaten Jombang - Nurwati, Butet (Universitas Nusantara PGRI Kediri, 2022)
This study aims to determine the improvement of teachers' ability in compiling learning outcomes test questions during the pandemic through Principal Supervision activities with online group discussions techniques at the Jombang Islamic Boarding School State Elementary School in the odd semester of the 2020-2021 school year. This is based on the results of supervision carried out by researchers as school principals on the ability of teachers at SDN Pesantren, Tembelang District, Kab. Jombang, pointed out that the frequency of teachers in compiling questions during the pandemic was still guided by the existing LKS. This means that the teachers arrange the questions by taking the whole, or part of the questions in the LKS used. In addition, teachers at this school also use tests that have existed in previous years and are then adjusted to the teaching materials. This research was carried out at SDN Pesantren Jombang in the first semester of the 2020-2021 academic year for three months, namely July, August, September 2020 with the research subject of 8 class teachers and subject teachers. Methods of data collection using the method of documentation and observation. The conclusion of the results of this study is that the Principal's Supervision activities with online group discussion techniques can improve the ability of teachers in compiling learning outcomes test questions during the pandemic at the Pesantren State Elementary School, Tembelang District, Jombang Regency in the odd semester of the 2020-2021 school year.